2012
DOI: 10.1515/polyeng-2012-0056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing variables on mechanical properties of montmorillonite clay/unsaturated polyester nanocomposite using Taguchi based grey relational analysis

Abstract: The present investigation addresses the influence of process variables on the mechanical properties of montmorillonite (MMT) nanoclay with unsaturated polyester, using the mechanical shear mixing process. The rotational speed, mixing time, rotor blade design and clay content were chosen as process variables. The influence of these process variables on mechanical properties were studied with the help of grey relational analysis. Organically modified MMT nanoclay was used as the reinforcing filler, in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…By comparison, the T d in the LDPE-g-MA group is almost 10 8C above that in the LDPE group, and the other T d values at different clay contents showed no significant difference. Our observations related to the thermal stability of the composites samples are in good agreement with the results reported in the literature [27,28]. It appears that the dispersion degree and thermal stability of composites both increase because of the presence of the MA grafts along the polymer chains.…”
Section: Thermal Stability Examinationsupporting
confidence: 92%
“…By comparison, the T d in the LDPE-g-MA group is almost 10 8C above that in the LDPE group, and the other T d values at different clay contents showed no significant difference. Our observations related to the thermal stability of the composites samples are in good agreement with the results reported in the literature [27,28]. It appears that the dispersion degree and thermal stability of composites both increase because of the presence of the MA grafts along the polymer chains.…”
Section: Thermal Stability Examinationsupporting
confidence: 92%
“…It shown that, the fillers have high aspect ratio and it allows the larger interface area which increases the reinforcing effect. Several researchers have proved that the polymer composite prepared by incorporation of fillers like montmorillonite [23,24], CaCO3 [25], Al2O3 [26], TiO2 [26], talc [28], graphene [29] and carbon nano tubes [30] show the notable development in mechanical, thermal, physical properties and degradability compare to normal composites. The addition of filler in different scaling like nano and micro meter can also influence the structure-property relationships based on their dispersion ability with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of fillers in the reinforced composites changes the base property of the actual material [31]. Montmorillonite nanoclay (MMT-NC) is the most promising filler found to enhance the mechanical, thermal and electrical properties and also reduces the water absorption [23][24]32,33]. Eggshell powder (ESP) is an inorganic bio-filler and suitable reinforcement in plastic/polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of nanoclay on the electrical resistivity of various polymer matrices has already been studied [67,68]…”
Section: Resistivity Measurementmentioning
confidence: 99%